EFEKTIVITAS PENANGANAN KELUHAN PUBLIK DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PULAU TALIABU PROVINSI MALUKU UTARA - ALIANI, GUSMAN; OGOTAN, MARTHA; TULUSAN, FEMMY (Sam Ratulangi University, 2019)
Public services generally focus on a very broad aspect of life. In the life of the state, the government must provide a variety of community services needed by the community, ranging from services in the form provided or other services in order to meet the needs of the community in fulfilling population data and civil registration. Various public reform movements carried out by the government, but still there is pressure from the public to be accelerated. The quality of public services is provided by the government. Also complaints from the community can vary from community to the assistance provided may vary by all communities, furthermore specifically for population services it becomes more popular in the community. Making population services the most, representing the community. Note the District Civil Service Office of Taliabu Island Regency has received the title of permit for administration of population administration and civil registration, in fact in Pulau Taliabu Regency there is still a connection with population administration and civil registration. The problems mentioned above are slower solutions. The administrative settlement process is related to population administration in addition to those carried out at the Population and Registration Office of the Civil Regency, Taliabu Island in the discussion of community complaints, not the availability of facilities or media in helping the community. An example is given a box of suggestions or input from the community on the services provided by the Population and Civil Registration Office of Taliabu Island, related to the implementation of population administration. Keywords: Effectiveness, Handling, Complaints Public